Transitioning to a sustainable development framework for bioenergy in Malaysia: policy suggestions to catalyse the utilisation of palm oil mill residues - Salleh S.F.; Mohd Roslan M.E.; Abd Rahman A.; Shamsuddin A.H.; Tuan Abdullah T.A.R.; Sovacool B.K. (BioMed Central Ltd, 2023)
Biogas; Climate change; Compressed natural gas; Developing countries; Ecology; Electric power transmission networks; Hydroelectric power; Hydroelectric power plants; Natural gasoline plants; Palm oil; Planning; Solar power generation; Solar power plants; Sustainable development; Waste management; Biomass power plants; Climate change mitigation; Electricity generation; Renewable energy development; Renewable energy source; Renewable resource; Solar photovoltaics; Substantial biomass; Biomass